2019
DOI: 10.1039/c9ra04943f
|View full text |Cite
|
Sign up to set email alerts
|

Tannic acid modulates intestinal barrier functions associated with intestinal morphology, antioxidative activity, and intestinal tight junction in a diquat-induced mouse model

Abstract: The concentration of 2.5 mg kg−1 TA can ameliorate diquat-challenged jejunal injury in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
(51 reference statements)
1
21
1
Order By: Relevance
“…Many studies were carried out with TA in mouse models where a concentration of 30 mg/kg of TA was used in PSAPP mice [44]. Another study showed that treatment with 10 mg kg −1 TA along with diquat in mice induced a non-significant difference in the mice body weight [45]. Targeting these cancer stem cells is a better method of cancer chemotherapy, as it prevents cancer recurrence by attenuating the formation of the cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were carried out with TA in mouse models where a concentration of 30 mg/kg of TA was used in PSAPP mice [44]. Another study showed that treatment with 10 mg kg −1 TA along with diquat in mice induced a non-significant difference in the mice body weight [45]. Targeting these cancer stem cells is a better method of cancer chemotherapy, as it prevents cancer recurrence by attenuating the formation of the cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting was performed as described in our previous study ( Wang et al, 2019 ). Tween-20, RIPA buffer, protease inhibitor cocktail, bicinchoninic acid assay, 5 × loading buffer, SDS-PAGE (sodium dodecyl sulfate polyacrylamide gel electrophoresis) gels kit, and horseradish peroxidase-linked secondary antibodies were purchased from Beyotime Biotechnology (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal inflammation caused barrier breakdown leading to the inflammation of the intestinal mucosa and impairment of integrity, allowing pathogenic bacteria, toxins, and antigens from the lumen to translocate into the bloodstream and cause several dysfunctional conditions [ 103 ]. Several studies have reported that polyphenols have the potential to modulate intestinal permeability [ 104 ], and although not directly tested with polyphenols from mango, the intake of gallotannins was shown to improve intestinal barrier integrity and function through the increase in zonula occludens-1 (ZO-1) mRNA expression in oxidative stress induced in a mouse model [ 105 ]. In another study of weaning piglets with a high frequency of diarrhea due to impaired tight junctions, tannic acid intake reduced diarrhea by up-regulating the expression of occludin and zonula occudens-2 (ZO-2) mRNA [ 106 ].…”
Section: Mango Polyphenols In Gastrointestinal Disordersmentioning
confidence: 99%